The Effect of External Debt on Emissions: Evidence from China - Bese, Emrah; Friday, Haven Swint; Özden, Cihan (International Journal of Energy Economics and Policy, 2020)
In this study, the effect of external debt (EXD – current US$) on carbon dioxide emissions (CO2 – metric tons per capita) is examined by taking the environmental Kuznets curve (EKC) hypothesis as a basis for China. The relationships between CO2, gross domestic product per capita (GDP – constant 2010 US$), square of GDP (GD), energy consumption (EM – kg of oil equivalent per capita) and EXD is examined. The autoregressive distributed lag (ARDL) model and nonlinear ARDL model are used to examine symmetric and asymmetric relationships between the variables respectively for the period of 1978 to 2014 by including a structural break. China has had a growing EXD to support economic growth especially after the 2008 financial crisis. The results show that EXD and EM significantly and positively affect emissions (EMS). The asymmetric relationship between growth (GW) and EMS is confirmed. The EKC hypothesis is not confirmed for China. The results of the study are in line with the current economic structure of the Chinese economy. The Chinese economy is still over reliant on construction, heavy industries and real estate. Although China's current EXD is 13% of GDP, EXD is growing because private companies and local governments continue to invest heavily in construction and real estate, and have increased borrowing from abroad to cover operational costs since the central government's deleveraging policies have made borrowing from domestic markets more difficult. Keywords: environmental Kuznets curve; external debt; China; nonlinear ARDL; ARDL JEL Classifications: Q4, Q5, O5 DOI: https://doi.org/10.32479/ijeep.10605